2018
DOI: 10.1021/acs.orglett.8b02923
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Three-Component Umpolung Synthesis of 1,3-Diamines

Abstract: A visible-light-mediated photocatalytic umpolung synthesis of 1,3-diamines from in situ-generated imines and dehydroalanine derivatives is described. Pivoting on a key nucleophilic addition of photocatalytically generated α-amino radicals to electron-deficient alkenes, this three-component coupling reaction affords 1,3-diamines efficiently and diastereoselectively. The mild protocol tolerates a wide variety of functionalities including heterocycles, pinacol boronates, and aliphatic chains. Application to biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 48 publications
0
49
0
3
Order By: Relevance
“…This report complemented the previous iridium-based photocatalytic approaches using the Karady-Beckwith alkene [ 156 , 157 ]. It also supplemented previous work involving the employment of halopyridines [ 156 ], N -alkyl tertiary amines [ 157 ], potassium phenoxymethyl trifluoroborates [ 158 ] or imines [ 159 ]. Starting with the protected dehydroalanine 215 , coupling was conducted in the presence of a Ru(bpy) 3 (PF 6 ) 2 catalyst and Hantzsch ester (HE) or methyl Hantzsch ester (MeHE) with a range of alkyl radical precursors (alkyl iodides, bromides and N -(acyloxy)phthalimides).…”
Section: Complex Fluorine-containing Non-aromatic Amino Acidsmentioning
confidence: 78%
“…This report complemented the previous iridium-based photocatalytic approaches using the Karady-Beckwith alkene [ 156 , 157 ]. It also supplemented previous work involving the employment of halopyridines [ 156 ], N -alkyl tertiary amines [ 157 ], potassium phenoxymethyl trifluoroborates [ 158 ] or imines [ 159 ]. Starting with the protected dehydroalanine 215 , coupling was conducted in the presence of a Ru(bpy) 3 (PF 6 ) 2 catalyst and Hantzsch ester (HE) or methyl Hantzsch ester (MeHE) with a range of alkyl radical precursors (alkyl iodides, bromides and N -(acyloxy)phthalimides).…”
Section: Complex Fluorine-containing Non-aromatic Amino Acidsmentioning
confidence: 78%
“…Previously, our group has reported that the use of bespoke Hantzsch ester reductants can modulate reactivity and in turn increase product yield and/or improve diastereoselectivity in reductive functionalization of imines . A survey of Hantzsch ester reductants (Scheme B, entries 2–4) demonstrated that methyl carboxyphenyl derivative ( HE4 ) led to increased conversion to product (90 %) and to a higher diastereomeric ratio (1.9:1, for further optimization details, see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, pioneer work employing iridium(III) photoredox catalysis has been made in this field in the past few years. However, these methods are restricted to the Karady‐Beckwith alkene or, for the more valuable acyclic α,β‐dehydroamino acids, to the use of halopyridines, N ‐alkyl tertiary amines, potassium phenoxymethyl trifluoroborates and imines as radical precursors and/or coupling partners. Aiming at a more general and less costly method, we herein present a ruthenium(II) photoredox‐catalyzed functionalization of dehydroamino acids and peptides with a broad variety of alkyl radical precursors, which allows to easily introduce fluorinated and fatty acid‐derived chain groups, as well as carrying on late stage peptide functionalization (Scheme c).…”
Section: Methodsmentioning
confidence: 99%